Evaluation of rotary file system (Kedo-S-Square) in root canal preparation of primary anterior teeth using cone beam computed tomography (CBCT)-in vitro study - Rasha H. Mohamed; Amina M. Abdelrahman; Aly A. Sharaf (BMC, 2022)
Abstract Background In recent years, pediatric endodontics has witnessed various advances including use of rotary files in pulpectomy. This study aimed to comparatively evaluate taper, amount of dentin removal and instrumentation time of the pediatric rotary Kedo-S Square file, hand K-files and H-files in primary canines using cone beam computed tomography (CBCT). Methods 60 primary canines were randomly assigned into three groups; A1 Kedo-S-Square rotary file (group I), hand stainless steel K file (group II) and hand stainless steel H file (group III). Teeth were mounted in vinyl poly siloxane impression material templates to be scanned before and after instrumentation by CBCT scans using Ondemand 3D software. Shaping ability of the files were evaluated in terms of taper of the canal and amount of dentin remaining of each group. Instrumentation time was recorded using a digital stopwatch. Results Kedo-S Square removed a significantly less amount of dentin in both apical (P < 0.002) and coronal thirds (P < 0.014). Taper of the preparations showed significant differences as Kedo-S Square file showed good taper in maximum number of root canals, while maual K- and H-files showed poor taper in maximum number of root canals (P < 0.0001). Rotary Kedo-S Square files required less instrumentation time (P < 0.0001). Conclusion The use of rotary Kedo-S Square files resulted in better conservation of tooth structure, superior tapering ability and least instrumentation time compared to hand K- and H-files.